Recapitulating X-Linked Juvenile Retinoschisis in Mouse Model by Knock-In Patient-Specific Novel Mutation - Chen, Ding; Xu, Tao; Tu, Mengjun; Xu, Jinlin; Zhou, Chenchen; Cheng, Lulu; Yang, Ruqing; Yang, Tanchu; Zheng, Weiwei; He, Xiubin; Deng, Ruzhi; Ge, Xianglian; et al. (Frontiers in Molecular Neuroscience, 2018)
X-linked juvenile retinoschisis (XLRS) is a retinal disease caused by mutations in the gene encoding retinoschisin (RS1), which leads to a significant proportion of visual impairment and blindness. To develop personalized genome editing based gene therapy, knock-in animal disease models that have the exact mutation identified in the patients is extremely crucial, and that the way which genome editing in knock-in animals could be easily transferred to the patients. Here we recruited a family diagnosed with XLRS and identified the causative mutation (RS1, p.Y65X), then a knock-in mouse model harboring this disease-causative mutation was generated via TALEN (transcription activator-like effector nucleases). We found that the b-wave amplitude of the ERG of the RS1-KI mice was significantly decreased. Moreover, we observed that the structure of retina in RS1-KI mice has become disordered, including the disarray of inner nuclear layer and outer nuclear layer, chaos of outer plexiform layer, decreased inner segments of photoreceptor and the loss of outer segments. The novel knock-in mice (RS1-KI) harboring patient-specific mutation will be valuable for development of treatment via genome editing mediated gene correction.